Radiographic and ultrasonographic imaging of a dystrophic mineralization on the oblique sesamoidean ligament in a jumping horse. Twenty months follow-up - Marilia Ferrari Marsiglia; Ana Lucia Miluzzi Yamada; Marcelo Pinheiro; Geissiane Moraes Marcondes; Nicole Fidalgo Paretsis; Luis Cláudio Lopes Correia da Silva (Brazilian Journal of Veterinary Research and Animal Science, 2020)
Mineralization of the anatomical structures involved in the limb movement of horses has been reported to induce lameness and interfere with athletic performance. A 4-year-old jumping horse in sport activity was reported at Veterinary Hospital of University of São Paulo, with mild lameness and a mineralized oblique distal sesamoidean ligament (ODSL) of the left forelimb, revealed by a purchase radiographic and ultrasound examination. Mineralization is more common in tendons than ligaments. This report calls for attention to these structures when performing image exams, even in mild lameness. Long-term favorable follow-up by ultrasonographic and radiographic examination showed that the severe ligament injury in this case did not decrease the athletic activity until the present day.